CR-MAC: Cooperative Relaying MAC Protocol for VANETs - Karabulut, Muhammet Ali; Shah, A. F. M. Shahen; Ilhan, Haci (IEEE, 2019)
In this paper, a novel cooperative relaying medium access control (CR-MAC) protocol is proposed for vehicular ad hoc networks (VANETs). Three data transmission modes have been offered to increase the throughput which are direct transmission (DT), cooperative relaying (CR) and multi-hop relaying (MHR). IEEE 802.11 standard defined mechanism only for design direct communication which is not suitable for cooperative relaying. Therefore, new control packets are defined and existing control packets format are modified for cooperative communication. An analytical model based on a Markov chain model is presented. Numerical results show that the proposed CR-MAC protocol increases the throughput.
Keywords: Cooperative communication; IEEE 802.11; MAC; optimum relay; VANETs; Computer Science; Engineering